Morusin shows potent antitumor activity for human hepatocellular carcinoma in vitro and in vivo through apoptosis induction and angiogenesis inhibition - Gao L; Wang L; Sun Z; Li H; Wang Q; Yi C; Wang X (Dove Medical Press, 2017)
Ling Gao,1,* Li Wang,2,* Zhen Sun,3 Haiyan Li,3 Qiaoping Wang,3 Cheng Yi,1 Xiujie Wang3 1Department of Abdominal Cancer, 2Laboratory of Lung Cancer, Lung Cancer Center, 3Laboratory of Experimental Oncology, West China Hospital, West China Clinical Medical School, Sichuan University, Chengdu, People’s Republic of China *These authors contributed equally to this work Abstract: Hepatocellular carcinoma (HCC) is one of the most aggressive cancers with high mortality worldwide. Research and development of novel agents for HCC therapy is in demand, urgently. Morusin has been reported to exhibit potential cytotoxic activity in several cancer cell lines. However, whether it has potential antiangiogenic activity especially in HCC remains unclear. In the current study, we found that morusin exerted growth inhibition effects on human HCC cells (HepG2 and Hep3B) in vitro and human HCC cell (HepG2) xenografts in vivo. Moreover, apoptosis induction was observed in a dose-dependent manner after morusin treatment along with an increase in the expression of active caspase-3 and the Bax/Bcl-2 expression ratio. More importantly, morusin inhibited proliferation, migration, and tube formation of human umbilical vein endothelial cells (HUVECs) in vitro and downregulated angiogenic proteins in HCC cells and HUVECs. In vivo, tumor angiogenesis was also attenuated after morusin treatment. In addition, morusin suppressed constitutive as well as IL-6-induced STAT3 phosphorylation in HCC cells and corresponding tumor tissues. Overall, morusin has a potential anticancer effect on human HCC cells in vitro and in vivo by inducing apoptosis and inhibiting anti-angiogenesis. The corresponding mechanism might be associated with the attenuation of the IL-6/STAT3 signaling pathway. Morusin might serve as a promising novel anticancer agent in HCC therapy, and requires further study. Keywords: morusin, human hepatocellular carcinoma, apoptosis, angiogenesis, IL-6, STAT3